Performance of chilli semerah (Capsicum annum) as influenced by different rates of nitrogen - Razali, Muhamad Adib (2015)
Chilli Semerah is a new variety of chilli species that is categorized as Capsicum annum. Chilli Semerah can produce yield that are matured at the same time, thus reducing the cost of labour to pluck the chilli fruits. This experiment was conducted at Ladang 10, Universiti Putra Malaysia (UPM), to determine the effect of different rates nitrogen (N) fertilizer on growth and yield of chilli Semerah. The experimental design that was used in this experiment was Randomized Completely Block Design (RCBD) with four replications. This experiment used four levels of N rates to get the best quantity of N fertilizer that are needed by the plants. The rates of N are 120, 180, 240 and 300 kg/ha. The source of N fertilizer is urea. Meanwhile, Triple Superphosphate (TSP) and Muriate of Potash (MOP) were used as the source of phosphate and potassium for the plants at recommended rates. The parameters measured are plant height, number of leaves, canopy diameter of the plants, number of branches, number of flowers, total number of chilli fruits, weight of chilli fruits and number of fruits set after first harvesting. Data collected were subjected to the analysis of variance (ANOVA) and Least Significant Difference (LSD) test. As a conclusion, nitrogen with Treatment 2 (180 Kg N ha-1) was recommended with further finding for increasing the yield production of Chilli Semerah.